Concealed by darkness: How stand density can override the biodiversity benefits of mixed forests - P.‐O. Hedwall (Ecosphere, 2019)
Abstract Higher tree species richness often increases the diversity of other taxonomic groups and is promoted in many managed forest systems. The reason for the higher diversity is due to, for example, inter‐specific differences in resource filtering of the trees. Resource filtering also depends on the total density of the tree layer, but the interaction between tree species composition and density is, so far, unexplored. Likewise, few studies have addressed whether mixtures of tree species host higher diversity, or support higher productivity, of other taxa than monocultures of the same tree species. We use a gradient in overstory tree species composition, ranging from pure Norway spruce (Picea abies) to pure Birch (Betula sp.), combined with a gradient from open to closed forest, to assess the joint effects of tree species mixture and forest density on the understory vegetation. The cover and species richness of understory vascular plants increased with an increasing proportion of birch and decreased with increasing forest density, while the cover of bryophytes decreased with an increasing proportion of birch and increasing forest density. There were clear interactions between tree species composition and forest density; the decrease in vascular plants with forest density was stronger in forest dominated by spruce than in forests dominated by birch, and the positive effect of an increasing proportion of birch was smaller in dense than in open forests. There were no indications of mixed forests supporting a higher species richness or plant cover than any of the two monocultures. Additionally, few species (10%) showed tendencies toward a higher probability of occurrence in mixed forests, and most of these also occurred in open pure stands. Our results indicate a potential conflict between goals for diversified forests and increased biomass production, as the positive effects for understory vegetation from mixtures may be lost to concomitant increases in forest density. Furthermore, the limited number of species benefiting from mixtures per se indicates that similar biodiversity benefits for understory vegetation may be obtained at landscape levels from the increased use of broadleaf and lower‐density production stands, as from mixtures.